The Graph Theoretical Approach to Bankruptcy Prediction: Array - Choe, Kwangseek; Garas, Samy (The Journal of Accounting and Management, 2020)
Objectives – This paper explores the applicability of the graph theoretical methods to bankruptcy prediction. Prior Work – Various statistical techniques have been used to predict business failure including univariate analysis, multivariate discrimination analysis, logit model, probit model, and neural networks. Approach – This paper employs undirected graph and matrix methods based on the Graph Theory. Results – The empirical findings confirmed the validity of the proposed methods for predicting bankruptcy. Implications - The proposed method in this paper provides an insight into the development of a new approach to the assessment of financial solvency of a company. Value – This paper contributes to the literature by introducing the graph theoretical approach to bankruptcy prediction.